Socialization of the Application of a Combination of Problem-Based Learning and Numbered Head Together Learning Models in Increasing Student Learning Motivation - Ali Usman; Moch. Hatip; Wahyu Eko Widianto; Dzarna Dzarna; Vizza Az Zahra Al Laros; Siti Wulandari (Universitas Muhammadiyah Jember, 2024)
A learning model is a framework designed to help create an effective learning environment. Furthermore, learning motivation is an encouragement for students to be able to participate actively in the learning process. Socialization of the application of a combination of Problem-Based Learning (PBL) and Numbered Heads Together (NHT) learning models in increasing student learning motivation. This research method includes socialization and mentoring. Socialization delivers material related to PBL, NHT learning models, and student learning motivation. Mentoring is practiced, and further explanation is provided regarding applying PBL and NHT learning models to increase student learning motivation. The PBL and NHT learning models are effective learning models in encouraging student learning motivation. This increase in student learning motivation is caused by the structure of learning steps implemented in the PBL and NHT models. Each step in this model is designed to provide a meaningful learning experience, which consistently can increase student learning motivation. Thus, the systematic and sustainable application of the PBL and NHT models can significantly increase student learning motivation. Teachers are encouraged to use various learning models, including PBL and NHT, to increase students' learning motivation in the learning process. Teachers are expected always to apply appropriate learning models to achieve learning goals.